2016
DOI: 10.3233/jad-150625
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Mild Cognitive Impairment Subtypes for Dementia and Mortality: Data from the NEDICES Cohort

Abstract: Those with aMd-MCI were at greatest risk of progression to dementia, as in other surveys and might be explored with increased attention in MCI research and in dementia preventive trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 88 publications
3
54
0
Order By: Relevance
“…Several surveys with similar MCI definitions to our study, but with a more extensive psychometric evaluation also showed similar results [10,[39][40][41]. The aMd-MCI is the only stable MCI subgroup in our longitudinal clinical investigation [evolution to more cognitive decline or dementia (15.6%), persistent MCI (35.7%), evolution to CN (10.1%), the rest were dead or ineligible subjects].…”
supporting
confidence: 80%
See 2 more Smart Citations
“…Several surveys with similar MCI definitions to our study, but with a more extensive psychometric evaluation also showed similar results [10,[39][40][41]. The aMd-MCI is the only stable MCI subgroup in our longitudinal clinical investigation [evolution to more cognitive decline or dementia (15.6%), persistent MCI (35.7%), evolution to CN (10.1%), the rest were dead or ineligible subjects].…”
supporting
confidence: 80%
“…This big research is going on, investigating the evolution of AD from an initial population of cognitively normal subjects (n=200), MCI (n=400) and AD patients (n=200) with sophisticated CSF biomarkers (beta-amyloid, tau) and neuroimaging (MRI, PET) [7][8][9][10][11]. The study begins in 2005 with the enrollment of 800 participants from 56 clinical sites of the United States and Canada.…”
Section: In the Clinical Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…In a population of older adults free of dementia, mortality was 52% greater in persons with the lowest memory score (0) in the 3‐word recall item of the MMSE vs. persons with the highest score (3) . Amnestic MCI has been found to be associated with a higher risk of mortality . Several hypotheses can be proposed about the association between memory deficits and survival; persons with memory deficits may underreport signs or symptoms, leading to late diagnosis of diseases affecting survival; another hypothesis is that altered memory reflects alteration in brain structure/functioning (i.e., reduced cognitive reserve due to ischemic lesions and/or B‐amyloid deposition) and its control of physiological systems by neurotransmitters and hormones which could affect survival.…”
Section: Resultsmentioning
confidence: 99%
“…16 Amnestic MCI has been found to be associated with a higher risk of mortality. 17 Several hypotheses can be proposed about the association between memory deficits and survival; persons with memory deficits may underreport signs or symptoms, leading to late diagnosis of diseases affecting survival; another hypothesis is that altered memory reflects alteration in brain structure/ functioning (i.e., reduced cognitive reserve due to ischemic lesions and/or B-amyloid deposition) and its control of physiological systems by neurotransmitters and hormones which could affect survival. Finally, memory can reflect cognitive frailty due to the presence of depression, use of anticholinergic medications, polypharmacy, infections, sleep problems and other conditions associated with higher mortality risk.…”
Section: Resultsmentioning
confidence: 99%